Arab women in management and leadership stories from Israel - Arar, Khalid; Shapira, Tamar; Azaiza, Faisal; Herts-Lazarovits, Raḥel (Palgrave Macmillan, 2013)
This book follows the stories and experiences of 22 Arab women who have overcome patriarchal societies to create their own path to management and leadership in the areas of education and welfare.